A Study of Rocket Exhaust Particles - Dennis, C. W. (Cranfield University, 1996)
The exhaust -plumes generated by rocket motors are of significant military importance for missile detection, recognition and communication due to their electromagnetic emission and propagation properties. The plume is a high temperature, high velocity stream of gas and particles, into which the surrounding air is entrained. With improvements in the modelling of plume gas chemistry and turbulence, particles present in the plume have become more important in the computational prediction of the plume's flow field, and the subsequent prediction of plume emission and propagation characteristics. This thesis describes research on plume particles, including the measurement of their physical characteristics and the addition of two phase coding (ie. particles) into current plume prediction software. Particle collections were carried out in plumes produced by rocket motors with double base and composite propellants (including aluminised). The collected particles were analysed to establish their chemical composition and size distribution. A laser Doppler anemometer system was successfully used to measure particle velocities in the plumes of 1.5kN double base motors. Particle tracking software was used to trace the paths of particles using a simplified prediction of the plume and it was found that the predicted particle behaviour was analogous to that measured experimentally. Project management software was used during the research and its relevance was assessed in respect to the project's size and nature. The management of experimental trials was studied and a methodology formulated to help improve their future operation. The costs and benefits of the research were assessed and compared to other research projects. Many of the benefits gained, such as measurement techniques, require marketing to ensure that they are exploited in the future. Recommendations for future research are given that should enhance the present work.